Complications after colonoscopy and surgery in a population-based colorectal cancer screening programme. (September 2016) - Saraste, Deborah; Martling, Anna; Nilsson, Per J; Blom, Johannes; Törnberg, Sven; Hultcrantz, Rolf; Janson, Martin
Objectives: To report complications after colonoscopy and surgery in patients with neoplasia detected through a population based colorectal cancer (CRC) screening programme in the capital region of Sweden. Methods: Patients who after a positive FOBT screening result underwent colonoscopy from 1 January 2008 to 30 June 2012 were included. Mortality and complications within 30 days after colonoscopy or subsequent surgery were identified through national registers, and complications were assessed through review of medical charts. Complications were graded using the Clavien-Dindo classification. Results: After 2984 colonoscopies, the complication rate was 1%. The risk of post-polypectomy bleeding was 14/1000. The risk of perforation was 1/1000 after a diagnostic colonoscopy and 2.5/1000 after a colonoscopy with polypectomy. One patient developed a post-polypectomy syndrome. There was one death which was not related to the colonoscopy. After surgery for 37 adenomas and 155 CRCs, the total complication rates were 27% and 50%, respectively. The rate of anastomotic leakage was 13% and 12% after surgery for adenomas and CRC, respectively. There were no deaths after surgery. The overall complication rate after colonoscopy and surgery for adenomas and cancer was 4%. Conclusions: Overall complication rates were acceptable and mortality low; however, the rate of anastomotic leakage after surgery for both adenomas and CRC was higher than expected.